Implementasi Sistem Aplikasi dan Metode Pembelajaran Paikem Gembrot Berjas (Berbasis Jaringan Sosial) - Rayung Wulan; Eddy Saputra; Nur Ali (STRING (Satuan Tulisan Riset dan Inovasi Teknologi), 2017)
The process of learning in the educational unit organized an interactive, aspirational, fun, challenging, motivating the students to actively participate and provide enough space to for innovation, creativity, and independence according talents, interests, and physical development, as well as psychological protégé. " making educators are increasingly challenged to manage the class, with the help of props teaching approach (approach to teaching) that is shared is used along with a lot of specific methods and with different teaching media that accompanied the arrangement of the classroom and the seating of students such that the learning process becomes active , innovative, creative, effective, and fun. Thus, the students were interested and easily absorb the knowledge and skills that are taught. The development of information and communication technology currently allows PAIKEM fat BER JAS term suits means-based social networking (Internet). At the present time has been so much infrastructure, Information and Communication Technology which none.And community (including students) are already familiar with the technology and knowledge needed extra to use the technology. With the help of social networks based tutorial educators make it easier to demonstrate directly to students.